The Effect of Oxytocin and Marmet Massage on Exclusive Breastfeeding: A Continuity of Care Case Study - Umar, Mareza Yolanda; Wardani, Psiari Kusuma (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Continuity of care (COC) represents comprehensive midwifery services throughout pregnancy, childbirth, postpartum, and family planning. The perinatal period, spanning from conception to 12 months postpartum, is associated with a higher probability of health complications. A fundamental strategy to decrease the maternal mortality rate is to alleviate the labor pain experienced by women, as almost one-fifth of all maternal deaths occur more than six weeks post-delivery. Midwife-led continuity of care diminishes women's apprehension around labor and postpartum depression, while simultaneously promoting exclusive breastfeeding. The objective is to deliver uninterrupted midwifery care to moms by employing Oxytocin Massage and Marmet Massage during the postpartum phase. This is a case study using qualitative analysis involving three pregnant women in the third trimester who received continuous midwifery care throughout pregnancy, labor, the immediate postpartum period, and family planning from October 2023 to February 2024. Qualitative data analysis was conducted thoroughly and persistently till finalization. The administration of oxytocin massage and the Marmet technique to mothers following observational assessments resulted in an augmentation of breast milk production volume, consistent with previous literature and demonstrating alignment between theory and practice. The midwifery profession aspires to advance sustainable midwifery care grounded in existing evidence and to adopt sustainable therapeutic practices alongside complementary interventions.